Destroying Democracy - Duncan, Jane; Gordon, Linda; Kaaf, Gunnett; McKinley, Dale; Nilsen, Alf Gunvald; Pillay, Devan; Radebe, Mandla J.; Saad-Filho, Alfredo; Satgar, Vishwas; Solty, Ingar; Williams, Michelle (Wits University Press, 2021)
Destroying Democracy, volume six of the Democratic Marxism series, focuses on how decades of neoliberal capitalism have eroded the global democratic project and how, in the process, rising authoritarianism is expressing itself in divisive and exclusionary politics, populist political parties and movements, increased distrust in fact-based information and news, and the withering accountability of state institutions. Over the last four decades, democracy has radically shifted to a market democracy in which all aspects of human, non-human and planetary life are commodified and corporations have become more powerful than states and their citizens. This is how neoliberal capitalism functions at a systemic level and if left unchecked is the greatest threat to democracy and a sustainable planet. The authors home in on four country cases – India, Brazil, South Africa and the United States of America to interrogate issues of politics, ecology, state security, media, access to information and political parties, and affirm the need to reclaim and re-build an expansive and inclusive democracy. The book is an invaluable resource for all who are interested in understanding the threats to democracy and the rising tide of authoritarianism in the global south and the global north.